Nurse perception of nursing handover at the University Clinical Hospital in Zagreb - Režić, Slađana (Array, 2019)
Introduction. Nursing handover refers to communication occurring between two shifts of nurses with the specific purpose of handing over information about patients under the nurses’ care. Several styles of nursing handover exist, whereas in Croatia written handover is legally required. Aim. The aim of the study was to examine nurses’ perception of the nursing handover: whether nursing handover improves patient safety, whether the content of the handover influences the quality of nursing care and whether the handover is important for continuity of nursing care. The aim was also to determine how the nursing handover is performed, how long it takes and whether written instructions are necessary for the nursing handover. Methods. The study was conducted between 1 October 2017 and 30 October 2017. The study was conducted on the basis of a questionnaire made specifically for this purpose. The questionnaire consisted of 14 questions. The first part of the questionnaire referred to the participants’ demographic data: years of service, age, gender, education level, workplace; the second part of the questionnaire referred to nurses’ perception of the nursing handover. Results. The questionnaire was filled in by 295 nurses. Out of this number, 40 were male and 255 female nurses. The majority of participants finished secondary education and have been working between 11 and 20 years. In most cases, nursing handover is recorded in electronic written form and also at the patient’s bedside. Over 90% of participants feel that the handover contributes to improved patient safety and quality of care. Conclusion. Nursing handover is recorded in electronic written form, as well as at the patient’s bedside on all wards that participated in the study. This form of handover ensures better continuity of care, improves patient safety and reduces loss of vital information. The need to draw up written instructions for the nursing handover was determined.